BLACK RICE ETHANOL EXTRACT EFFECT ON ACCUMULATION OF LYMPHOCYTES IN LIPOPOLYSACCHARIDE-INDUCED WISTAR RATS SPLEEN - Henny Juliastuti; Welly Ratwita; Meyra Aretha Ridzki (Journal of Health and Dental Sciences, 2023)
Infectious diseases are the second leading cause of death in the world after cardiovascular disease. Chronic infections were caused by anaerobic gram-negative bacteria that contain lipopolysaccharides which function as the primary defense of bacteria against antibiotics and antimicrobials. These bacteria can cause chronic inflammation. Chronic inflammation can lead to the accumulation of lymphocytes in the spleen, which plays a role in the immune system. An adequate immune system is needed to overcome these infections through immunostimulators, one of which was obtained from anthocyanins derived from black rice (Oryza sativa L.indica). This study aims to determine the effect of black rice ethanol extract on the spleen of Wistar rats induced by lipopolysaccharide. This study is an experimental laboratory study with a sample of 27 rats given 400 mg/kg BW black rice extract for 14 days; then, rats were induced with LPS 0.3 mg/kg BW intraperitoneally for 24 hours before being CO2 euthanized, and the spleen was taken to examine the diameter of the lymphoid follicles. The design of this research is the Posttest Only Control Group. The results were analyzed using the One-way ANOVA test with a p-value <0.05, meaning that there was a significant difference in the diameter of the lymphoid follicles between the treatment groups. The results showed that the diameter of the lymphoid follicles in the treatment group was more extensive than that in the positive and negative control groups. In conclusion, the ethanolic extract of black rice can increase the accumulation of lymphocyte cells in the white pulp zone, thereby increasing the diameter of the lymphoid follicles in the spleen of Wistar rats induced by lipopolysaccharide. DOI : 10.54052/jhds.v2n3.p415-428